إثبـــات الجـريمــة الجـمــركيــة - قاســمــــي, محـمـد عبـد الـوهــاب (جامعة الوادي University of Eloued, 2017)
لـقـد وضع المشــرع طـرق إثبـات خاصة للجريمة الجمركيــة في قانــون الجمارك الجزائــري و المتمثلة في المحاضر الجمركية من محضر حجز و محضر المعاينة كما أضفى المشرع على هذه المحاضر حجية خاصة و قوة إثبات من خلال المادة 254 قانون جمارك و غيرها ،حيث لا يمكن الطعن فيها إلا بالتزوير أو عن طريق إثبات العكس بالنسبة للمحاضر ذات الحجية النسبية و لكي تكتسب هذه المحاضر الحجية وضع لها شروط شكلية و موضوعية بحيث أن تتوافر فيها بالإضافة إلى إجراءات الطعن بالتزوير في هذه المحاضر أمام الجهات القضائية المختصة. بالإضافة إلى المحاضر الجمركية يتم إثبات الجرائم الجمركية بكافة الطرق القانونية و هذا تأكيدا للمادة 212 من الأمر رقم 66/155المعدل و المتمم و المتضمن قانون الإجراءات الجزائية الصادر في:1966/06/08 و التي تنص على أنه " يجوز إثبات الجرائم بأي طريقة من طرق الإثبات الأخرى، و تتمثل في محاضر الشرطة القضائية و إجـراءات التحقـيق أمام القـضـاء و القرائـن القانونية الجمركية و الخبرة و الاعتـرافـــات و الشهادة. و يعد الإثبات في الجريمة الجمركية المجال الخصب والواسع للقرائن وبالخصوص القرائن القانونية، مما جعل المشرع يتدخل في قانون الجمارك بقرائن أخرى يفترض بموجبها قيام الجريمة في حق المتهم،و ان كان للقاضي الجزائي مطلق السلطة التقديرية في تقدير و وزن أدلة الإثبات في جرائم القانون العام،مع مراعاة أحكام المادة 213 قانون الإجراءات الجزائية التي تنص على أن " الاعتراف كجميع عناصر الإثبات، يترك لحرية تقدير القاضي " و نشير في الأخير أن التشريع الجزائري يتفق مع التشريعات الفرنسية و المغاربية من حيث الحد من السلطة التقديرية للقاضي في مجال الإثبات الجمركي، إذ تضمنت كل هذه التشريعات أحكاما مطابقة لأحكام المادة 254 قانون جمارك الجزائري و هي مستمدة كلها من التشريع الجمركي الفرنسي. The legislator has established special methods of proof of customs crime in the Algerian Customs Code, which is the customs records of the minutes of the booking and the minutes of the inspection. The legislator also provided these records with special authority and the force of proof through Article 254 Customs Law and others, Or by proving the contrary in relation to the relevant authoritative records. In order to acquire these authentic records, they have formal and objective conditions, in addition to the procedures for countering fraud in these records before the competent judicial authorities. In addition to the customs records, customs offenses are proven by all legal means. This is an affirmation of Article 212 of Order No. 66/155 amended and supplemented by the Code of Criminal Procedure issued in 1966/06/08, which stipulates that " The other evidence, which is the records of the judicial police, the procedures of investigation before the judiciary, the customs evidence, experience, confessions and testimony. The evidence in the customs crime is the fertile ground for evidence and in particular the legal evidence, which makes the legislator intervene in the Customs Law with other grounds according to which the crime is committed against the accused. If the criminal judge has absolute discretion in assessing and weighing evidence of public law crimes, Taking into account the provisions of Article 213 of the Code of Criminal Procedure, which states that "recognition, like all elements of evidence, is left to the discretion of the judge" Finally, Algerian legislation conforms to French and Maghreb legislation in terms of limiting the judge's discretion in the field of customs proof. All these legislations contain provisions in conformity with the provisions of Article 254 of the Algerian Customs Code, which are derived from the French customs legislation.
قانــون أعمــال
Keywords: إثـبــات الـجـريـمــة - الجريمــة الجمركية – محاضر الشرطـة القضائيـة - محضر الحجز – محضر المعاينة - إجراءات التحقيـق - القرائن القانونية – الخـبـرة – الاعتراف – الشهادة.; the customs crime – proof of customs crime – the records of the judicial police – the minutes of the booking – the minutes of the inspection – The other evidence – the procedures of investigation before the judiciary– the customs evidence – experience – confessions – testimony.